The Communicative Approach To Identifying Text Units: Traditional And Contemporary Perspectives - Kushbakova Mukhayyo Azamatovna (Open Academia, 2026)
This article examines the problem of identifying text units from a communicative perspective. The study provides a comparative analysis of traditional and modern approaches to text unit identification and evaluates their methodological potential. While traditional approaches primarily rely on structural and formal criteria, modern approaches emphasize the role of communicative, pragmatic, and discourse-related factors. The findings demonstrate the theoretical and practical significance of the communicative approach in text analysis.
Keywords: text units; communicative approach; discourse; pragmatics